2018
DOI: 10.1021/acschemneuro.8b00182
|View full text |Cite
|
Sign up to set email alerts
|

Structural Basis of Small Molecule Targetability of Monomeric Tau Protein

Abstract: The therapeutic targeting of intrinsically disordered proteins (IDPs) by small molecules has been a challenge due to their heterogeneous conformational ensembles. A potential therapeutic strategy to alleviate the aggregation of IDPs is to maintain them in their native monomeric state by small molecule binding. This study investigates the structural basis of small molecule druggability of native monomeric Tau whose aggregation is linked to the onset of Tauopathies such as Alzheimer's disease. Initially, two ava… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 47 publications
2
19
0
Order By: Relevance
“…Methylene Blue did not show any apparent interaction with tau K18 M in 2D [ 1 H-15 N] SF-HMQC NMR spectra (Figure 1), whereas an interaction was identified by MST (K D 50 +/− 4 nM) ( Figure 2). Previously, it has been reported that Methylene Blue interacts with wild type tau K18(C291,C322) with a K D of 125.8 +/− 5.4 nM, as determined by MST [48], which is broadly consistent with the value determined in our study. Previous investigations of wild type tau K18 have also suggested that the Cys residues may be involved in binding Methylene Blue [25,48].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Methylene Blue did not show any apparent interaction with tau K18 M in 2D [ 1 H-15 N] SF-HMQC NMR spectra (Figure 1), whereas an interaction was identified by MST (K D 50 +/− 4 nM) ( Figure 2). Previously, it has been reported that Methylene Blue interacts with wild type tau K18(C291,C322) with a K D of 125.8 +/− 5.4 nM, as determined by MST [48], which is broadly consistent with the value determined in our study. Previous investigations of wild type tau K18 have also suggested that the Cys residues may be involved in binding Methylene Blue [25,48].…”
Section: Discussionsupporting
confidence: 92%
“…Previously, it has been reported that Methylene Blue interacts with wild type tau K18(C291,C322) with a K D of 125.8 +/− 5.4 nM, as determined by MST [48], which is broadly consistent with the value determined in our study. Previous investigations of wild type tau K18 have also suggested that the Cys residues may be involved in binding Methylene Blue [25,48]. However, our MST results using mutated tau K18 (tau K18 M ), which lacks these Cys residues, showed a similar interaction suggesting that the Cys residues are not critical.…”
Section: Discussionsupporting
confidence: 92%
“…Indeed, in a related study, we applied HT-CM-SPR screening for small molecules interacting with monomeric full-length tau, which resulted in the discovery of a variety of compounds which were able to reduce the aggregation of tau in vitro and in a cell model 23 . Hence, these studies add to the accumulating evidence that small molecules can bind to IDPs, such as αSyn 20 , tau 23,53 and the Aβ peptide 54 , despite their overall lack of persistent 3D structures.…”
Section: Discussionmentioning
confidence: 78%
“…Pose prediction accuracy studies on GSK3β inhibitors demonstrated that cognate docking calculations successfully reproduced crystallographic poses with RMSD less than 2 Å, while cross-docking calculations produced poses that deviate from X-ray poses providing valuable insights into computational structure-based design [156]. The structural basis of targetability of monomeric Tau by small molecules was studied using molecular docking indicating the ability of small molecules, like methylene blue, to bind to monomeric Tau and influence interactions of the protein with itself and other proteins [157]. Computational pharmacophore models, molecular docking, and MD simulations were employed to identify hyperphosphorylated sites of Tau including multiple serine sites changing the flanking sequence of R1/R2 repeats, which affects binding of Tau to microtubules [158].…”
Section: Cadd For the Development Of Anti-tau Inhibitorsmentioning
confidence: 99%